ANALISIS PENENTUAN HARGA JUAL BERDASARKAN METODE COST- PLUS PRICING DENGAN PENDEKATAN FULL COSTING - Yuli Yuli; Ernie Riswandari (Universitas Bunda Mulia, 2017)
The purpose of this paper is to determine whether the determination of the selling price by PT. Logamarta Asriprima adequate when compared with the determination of the selling price based on cost-plus pricing method and to find out if there is a difference between the selling price determination PT.Logamarta Asriprima done by determining the selling price based on cost plus pricing method. This type of research in this writing is descriptive. The method of analysis in this paper is as follows: first, to explain the determination of the selling price applied by companies to collect various fees in determining the selling price of the company, the second, calculate the size of the company's cost by dividing the total cost to the company's production capacity. third, calculate the price based on cost-plus pricing method based on a full cost approach; fourth, compare prices with the company selling the determination based on the study of theory, fifth; analyze the normal selling price difference which company to use to study the theory based on cost plus pricing method, the sixth ; determine the selling price applied by calculating the difference in selling price of either company. The determination of the selling price by PT. Logamarta Asriprima inadequate treatment due to differences in marketing costs other than that there is a difference between determining the selling price of a company with a study of the theory of Rp 510, - for this type of incandescent lamp 55 PS & Rp 640, - for this type of incandescent PS 47. companies should review the method of determining the selling price applied during this time, taking into account the cost plus pricing method in determining the selling price of cost plus pricing method that provides more accurate information for decision-makingKeywords: selling price, cost plus pricing, approach to full costing